Intrauterine growth restriction according to Peruvian customized curves: validation and diagnostic accuracy study - Tipiani-Rodríguez, Oswaldo (2024)
Introduction: There is no consensus on the growth curve to be used to assess fetalgrowth. Objectives: To validate customized curves and study their performancein the detection of neonates with intrauterine growth restriction (IUGR), as wellas their diagnostic accuracy. Methods: Initially, customized curves were designedwith 2,792 singleton fetuses from low-risk pregnancies; the optimal weight at 40weeks = 1,496.202 + (64.379 x fetal sex) + (831.362 x maternal length) + (9.567 xpregestational weight) was calculated and combined with a standard proportionalityfunction to adjust the weights according to gestational age. Subsequently, itsperformance was evaluated by applying it in a retrospective cohort of neonates aged24–40 weeks born between 2018-2022 in a tertiary hospital in Lima-Peru. Twins andcongenital anomalies were excluded. Results: A total of 6,598 neonates were studied.Customized curves showed good agreement with INTERGROWTH-21 (IG21) (kappa= 0.68; 95%CI = 0.62-0.74). They detected 2.8% of IUGR (184/6,598), similar to the3.1% for IG21 (205/6,598). They showed high specificity and negative positive value(NPV) (97% and 98%; 95%CI = 97-98% and 98-99%, respectively). The risk for perinataldeath (RR = 7.2; 95%CI = 4.6-11) and accuracy (96; 95%CI = 95-96%) were higher thanthose of the Fetal Medicine Foundation (FMF) (RR=3.6; 95%CI = 2.5-5.2 and accuracy=89%; 95%CI = 88-89%, respectively). Conclusion: The customized Peruvian curveswere reliable in assessing IUGR. Their detection capacity and diagnostic accuracywere similar to other international curves, although somewhat higher than those ofthe FMF.